The effect of different priming methods in breaking seed dormancy in date palm (Phoenix dactylifera L.) - Edogbanya, Ocholi Paul Ramallan; John, Joshua Ibe-Ojo; Obaje, Joseph Ojonugwa; Ekele, Jiata Ugwah; Matthew, Micah Onoruoyiza (Journal of Asian Scientific Research, 2023)
Seed dormancy is a phenomenon that prevents seeds from growing during adverse conditions. A number of factors may be responsible for this phenomenon, but one very common reason is the hardness of the seed coat as in the case of Date palm. This research was conducted to determine the effect of different priming methods on the rate of germination of date palm seeds. The treatments include cold water, hot water, H2SO4 and control in a cross randomized design. For the cold water treatment seeds were soaked for either 24, 48 or 72 hours; for the hot water treatment they were soaked for either 5, 10, or 15 minutes; and for the acid treatment they were soaked in 25 %, 50 % or 100 % of H2SO4 for 5 minutes. Twenty (20) seeds were selected for each treatment to carry out the germination experiment using moist absorbent paper. Data for germination rate was collected at 1, 2 and 3 weeks after planting (WAP). An optimal germination rate of 83% was observed at 3 WAP for the hot water treatment for 5 minutes. From this research, it can be concluded that priming generally increased the rate of germination of date palm seeds.